2007
DOI: 10.1590/s1415-65552007000200004
|View full text |Cite
|
Sign up to set email alerts
|

A orientação para o mercado sob a ótica da empresa e dos clientes na indústria hoteleira gaúcha

Abstract: A despeito do notório desenvolvimento da pesquisa no âmbito da orientação para o mercado nos últimos quinze anos, verifica-se a visão unilateral que os estudos têm imputado ao tema, baseada somente na percepção dos executivos da própria organização. Raros são os trabalhos que contemplam a perspectiva do cliente, além daquela das empresas, comparando-as. O objetivo deste artigo foi o de investigar as diferenças entre as auto-avaliações das empresas e as avaliações dos respectivos clientes, relativas ao grau de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(27 reference statements)
0
3
0
4
Order By: Relevance
“…The only inclusion criterion was that studies reported Sample. The 27 Brazilian articles used in this meta-analysis are: Antoni (2004), Carvalho (2001), Costa (2006), Dalmoro and Faleiro (2007), Faleiro (2001), Galão, Pacagnan, Silva and Frutos (2007), Gava and Silveira (2007), Gonçalves et al (2002), Mandelli (1998), Menna (2001), Müller Neto (2005, Perin (2002), Perin and Sampaio (2001, 2006, Perin, Sampaio and Faleiro (2002), Perin et al (2005), , Révillion (2005), Sampaio (2000), Santos and Rossi (2005), Silva, Damacena and Melo (2002), Slongo and Bossardi (2004), Souza (2004) and Urdan (2000Urdan ( , 2001aUrdan ( , 2001b.…”
Section: Study 1: Brazilian Meta-analysismentioning
confidence: 99%
“…The only inclusion criterion was that studies reported Sample. The 27 Brazilian articles used in this meta-analysis are: Antoni (2004), Carvalho (2001), Costa (2006), Dalmoro and Faleiro (2007), Faleiro (2001), Galão, Pacagnan, Silva and Frutos (2007), Gava and Silveira (2007), Gonçalves et al (2002), Mandelli (1998), Menna (2001), Müller Neto (2005, Perin (2002), Perin and Sampaio (2001, 2006, Perin, Sampaio and Faleiro (2002), Perin et al (2005), , Révillion (2005), Sampaio (2000), Santos and Rossi (2005), Silva, Damacena and Melo (2002), Slongo and Bossardi (2004), Souza (2004) and Urdan (2000Urdan ( , 2001aUrdan ( , 2001b.…”
Section: Study 1: Brazilian Meta-analysismentioning
confidence: 99%
“…Serious economic crises arose for the region's countries, with disastrous results for their populations (KLEIN, 2007). The adoption of business models that relied on the market to grow did not generate improvements or greater empowerment for consumers (GAVA and SILVEIRA, 2007), showing that, in the end, such models only helped to increase the hierarchy between companies and consumers -especially those of the Global North and of the Global South (FARIA, 2009), thus perpetuating Eurocentric hegemony (HARVEY, 2011). Market globalization did little to democratize consumption, because such global influences eventually produced more social inequality, class polarization, feelings of frustration and stress among consumers, materialism, and risks to health and the environment (GER, 1997).…”
Section: -609mentioning
confidence: 99%
“…Algumas limitações desta pesquisa estudo merecem consideração. Uma das mais relevantes é que o assunto pesquisado -Éticadá margem à ocorrência do chamado viés da desejabilidade social (ERFFMEYER; KELLOR; LECLAIR, 1999;GAVA;SILVEIRA, 2007). Este viés ocorre quando os participantes da pesquisa baseiam suas respostas no que percebem como uma resposta socialmente valorizada.…”
Section: Metodologiaunclassified